[Test Analyses Screening and Verification Instruments for Preschool Children. Volume II]. - Pennsylvania State Dept. of Education, Harrisburg; Pennsylvania State Dept. of Education, Harrisburg ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
This is the second of two volumes developed by Project CONNECT in order to enable local program personnel to determine the appropriateness of a test for a particular child. For 71 preschool tests the following information is presented, when available: title, whether the test is for screening or verification, bibliographic information, descriptive information, examinee appropriateness, administrative considerations, scoring and interpretation, implications for programming, normative data, technical aspects, references, and additional information. Test title and author indexes for both volumes are included. (MV)
ERIC Note: For related document, see ED 135 856.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Diagnostic Tests; Handicap Identification; Norms; Preschool Children; Preschool Education; Preschool Tests; School Readiness Tests; Scoring; Screening Tests; Test Interpretation; Test Reliability; Test Reviews; Test Selection; Test Validity; Tests; Project CONNECT; Guides, General